The Level of Knowledge of Healthcare Workers, Excluding Physicians, Regarding HIV, and Their Approach to People Living with HIV - Yurttaşer, Ercan; Çaçur, Orkun; Atakul, Onur; Görgülü, Yasemin; Şirin, Alperen; Yasin, Yeşim (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2020)
ABSTRACT Since its discovery, the Human Immunodeficiency Virus (HIV) continues to be a major health concern globally. Unofficial records show that over 14000 cases of HIV have been reported in Turkey, and this number is on the rise. People living with HIV (PLHIV) have become subjected to stigmatisation and discrimination all around the globe, including Turkey. This approach had a negative impact on PLHIV, especially in the healthcare industry. Previous studies, in Turkey and globally, have shown that healthcare workers lacked sufficient knowledge about HIV and PLHIV. Consequently, their approach to PLHIV was at times inappropriate and unequal. This study aimed to look at the level of knowledge of healthcare workers, excluding physicians, and their approach to PLHIV. A survey based on a questionnaire was conducted in 3 private hospitals in Istanbul, Turkey. A total of 161 participants-of which 67 were nurses, 54 were receptionists, 16 were laboratory technicians, 13 were physiotherapists, and 11 were caregivers-took part in this study. The questionnaire consisted of 14 total questions, divided into three sections; ‘Modes of HIV transmission’, ‘Protection from HIV transmission’ , and ‘HIV in the workplace’ . On average, 41% of healthcare workers lacked sufficient knowledge regarding modes of HIV transmission, and 48% lacked sufficient knowledge regarding protection from transmission of HIV. Furthermore, 48% had a different approach to PLHIV compared to other patients. Healthcare workers lack sufficient knowledge regarding HIV, and this reflects on their approach towards PLHIV. As a result of this stigmatisation, PLHIV are subjected to discriminative attitudes from the moment they set foot in a hospital environment. Therefore, educating healthcare workers about HIV is crucial to ensure that their approach to PLHIV is equal to that of other patients.